Numerical simulation of micro-cracked interface - Yong, Lip Men (2017)
Composite material with microscopically cracked interface between two different materials is modelled using interfacial micro-cracks which are taken to be periodically distributed over the whole interface. The ANSYS software is used to numerically simulate the micro-cracks under tensile loading and by applying the averaged displacement method as well as the energy approach. The interface stiffness of the interfaces were compared and estimated by two different approaches.